Challenges and opportunities of mesoscopic brain mapping with fMRI. (August 2021) - Bandettini, Peter A; Huber, Laurentius; Finn, Emily S
Highlights: At 7T, sub-mm voxel dimension functional imaging in humans is possible. Achieving sub-mm functional resolution requires pulse sequences sensitized to small vessels and tradeoffs in sensitivity, speed, and coverage. FMRI at this spatial scale requires single subject averaging due to low SNR and high spatial variability across subjects. Mapping layer activation and connectivity allows inferences of feedforward-feedback back activity and functional hierarchy. Abstract : Layer fMRI, requiring high field, advanced pulse sequences, and sophisticated processing methods, has emerged in the last decade. The rate of layer fMRI papers published has grown sharply as more groups are overcoming the substantial technical challenges and the unique advantages are becoming clear. Rather than simple delineation of functional activation, layer fMRI promises to provide directional activity and connectivity measures as they are inferred by the layer-specific location. This short review highlights the methods used to achieve layer fMRI as well as the challenges in acquisition, processing and interpretation. It emphasizes the utility of extensive individual averaging as well as the extreme difficulty of cross subject averaging. It also highlights recent studies that have explored layer fMRI in cognitive tasks as well as resting state connectivity studies that have revealed cortical hierarchy.